Investigating the venom components of the Giant Indian Centipede for Nav1.7 channel modifiers - Ngum, Neville Mvo (2019)
The electro-genesis property of voltage-gated sodium channels makes them indispensable therapeutic targets for numerous conductance disorders. The sodium channel (NaV)1.7 subtype expressed in sensory neurons in the dorsal root ganglia is thought to be a crucial signaling protein involved in nociceptive pain. Centipede envenomation results in instant rigid paralysis in prey and excruciating painful stings in humans. Compared to other venomous clades, these venoms have been largely ignored due to the minimal clinical significance of the stings. However, because many animal venoms are used to probe ion channels and some are progressing to becoming modern day venom-based drugs, we extracted the venoms of both male and female Scolopendra hardickei centipedes to evaluate their composition, to investigate activities at the NaV1.7 pain amplifying channel, and to search for the presence of pore forming toxins.